Inadvertent placement of an AXIOSTM stent connecting the duodenum to the renal collecting system - Sophia Humphrey, MD; Elias El-Haddad, MD; Driss Raissi, MD (Radiology Case Reports, 2025)
AXIOSTM stents are a new technology being utilized to transform the management of pancreatic fluid collections. Their novel anchoring mechanism intends to diminish unwanted complications such as stent malposition and migration. Though, even with this new mechanism, these remain prominent adverse events. Yet there is insufficient recognition within the literature of such events, as no cases have been reported of uncorrected stent misplacement into an unintended organ. We present a case of an AXIOSTM stent that was inadvertently placed into the extrarenal pelvis demonstrating the complexity of procedures when encountering atypical anatomy and the utility of additional imaging for intraprocedural guidance.